Novel sequential and simultaneous infrared-accelerated drying technologies for the food industry: Principles, applications and challenges. Issue 11 (26th April 2023) - Obajemihi, Obafemi Ibitayo; Cheng, Jun-Hu; Sun, Da-Wen
Abstract: Infrared drying (IRD) is considered an innovative drying solution for the food industry with advantages of energy-saving potentials, reduced drying time and production cost-effectiveness. However, IRD also suffers from drawbacks such as weak penetrative ability, and product overheating and burning. Therefore, over the years, significant progress has been made to overcome these shortcomings by developing infrared-accelerated drying (IRAD) technology based on the combination of IRD with other drying technologies. Although several reviews have been published on IRD, no review focusing on IRAD is yet available. The current review presents up-to-date knowledge and findings on the applications of IRAD technologies for enhancing the quality and safety of food. The fundamental principles and characteristics of IRAD, energy-saving potentials, simulation and optimization approaches for enhancing efficiency, and developments in various acceleration approaches by combining with other drying techniques for achieving better end-products are discussed, and challenges and future work for developing the novel accelerated drying technology are also presented. Due to the synergistic effects of sequential or simultaneous combined drying methods, the total drying time and energy required are drastically lowered with most IRAD technologies, and consequently there are significant improvements in the sensory, nutritional, and safety attributes of dried food products with better appearance and quality. The development of multi-wavelength IRAD systems based on infrared absorption bands, and the incorporation of novel sensing techniques for real-time monitoring during drying will further enhance process efficiency and food quality and safety.